1993
DOI: 10.4037/ajcc1993.2.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Determining AACN's research priorities for the 90s

Abstract: The American Association of Critical-Care Nurses completed a three-phased process of priority identification for critical care nursing research. In phase 1, a 78-item survey was generated following a comprehensive review of potential research topics. In phase 2, approximately 1000 critical care nurses rated each item on the survey for importance to critical care nursing. Based on these results, the AACN Research Committee formulated a clinical and a nonclinical (contextual) list of research topics. Each list c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Therefore, the authors conducted a preliminary study to identify and categorize the scope and nature of clinical decisions made by nurses in the coronary care unit (CCU) and coronary step-down (CSU) units as the basis for developing six representative hypothetical cases for this study. These cases were consistent with Benner's domains of nursing practice and AACN's research priorities (Benner, 1984;Lindquist et al, 1993).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Therefore, the authors conducted a preliminary study to identify and categorize the scope and nature of clinical decisions made by nurses in the coronary care unit (CCU) and coronary step-down (CSU) units as the basis for developing six representative hypothetical cases for this study. These cases were consistent with Benner's domains of nursing practice and AACN's research priorities (Benner, 1984;Lindquist et al, 1993).…”
Section: Introductionsupporting
confidence: 75%
“…Four reviews of critical care and coronary care nursing research indicated a need to investigate the practice complexities in these areas, but did not focus on clinical judgment nor explicate particular decisionmaking tasks (Foster et al, 1984;Kinney, 1984;Packa & Norris, 1987;Cowan, 1990). Similarly, a study sponsored by the American Association of Critical Care Nurses (AACN) revealed several clinical practice and contextual research priorities for the 1990s (Lindquist et al, 1993). Although relevant to understanding current critical care practices, these priorities did not reveal specific decision-making topics confronted by coronary care nurses.…”
Section: Introductionmentioning
confidence: 99%
“…All studies used some form of expert consensus method to generate the priorities and, as one would expect, the list of top priorities differs according to country and time when this was generated. Early studies among intensive care nurses in the United States (Lewandowski & Kositsky 1983, Funk 1989, Lindquist et al. 1993) and Australia (Daly et al.…”
Section: Introductionmentioning
confidence: 99%
“…Very few of the research priorities identified by Hong Kong critical care nurses were similar to those identified by American (Lindquist et al 1993), Australian (Daly et al 1996), andFinnish (Leino-Kilpi &Suominen 1997) studies. These studies highlighted prevention of pressure ulcers and nosocomial infections, prevention of burnout among nurses, staffing issues, and nursing standards, topics that were rated as being of low importance by Hong Kong critical care nurses.…”
Section: Discussionmentioning
confidence: 84%